Implementation of Lean Six Sigma in Pharmaceutical Inventory Control at Hospitals: A Literature Review - Damput, Fransiska Satriani; Sulistiadi, Wahyu (Syntax Corporation Indonesia, 2025)
Controlling drug inventory in hospitals plays an important role in ensuring the continuation of safe, timely, and efficient health services. However, problems such as overstock, out-of-stock, and inefficiency of the distribution process are often the main obstacles that still occur frequently. Lean Six Sigma in drug inventory control in hospitals is an approach that combines Lean and Six Sigma principles to improve efficiency, reduce waste, and decrease variation in the drug management process. The implementation of Lean Six Sigma aims to overcome problems such as stock out, overstock, and inefficient drug purchases, thereby improving the quality of pharmaceutical services in hospitals. Methods: This literature study used a combination of keywords